Modeling the Potential of Fortified Biscuits Too Address Micronutrient Deficiencies Among Preschool Children and Women in Cameroon (P10-116-19) - Woldegebreal, Demewoz (Curr Dev Nutr, 2019)
OBJECTIVES: To model the impacts of biscuits fortified with micronutrients (MN) on dietary nutrient adequacy among young children and women of reproductive age (WRA) in Cameroon. METHODS: In a nationally-representative survey stratified by macro-region (North, South, and Yaoundé/Douala), 24-h dietary recall data were collected from 843 children 12–59 months and 912 WRA. We simulated total MN intake under various scenarios using observed biscuit intake and addition of different amounts of vitamin A (VA) (200–600 µg Retinol Activity Equivalents (RAE)/100 g), folic acid (46–300 µg/100 g), vitamin B12 (0.74–2 µg/100 g), zinc (2–8 mg/100 g) and iron (5–15 mg/100 g) to biscuits. Usual intake distributions and prevalence of inadequate intake for each scenario were estimated using the National Cancer Institute method. RESULTS: Biscuits were consumed on the previous day by 11.2% of children nationally (4.5% South, 9.1% North, 20.7% Yaoundé/Douala) and 4.3% of WRA (1.5% South, 5.6% North, 5.9% Yaoundé/Douala). National baseline prevalence ± SE of inadequate intake among children was 59 ± 2% for VA, 49 ± 2% for folate, 85 ± 2% for vitamin B12, 70 ± 2% for iron, and 20–50% for zinc (depending on the cutoff used). Vitamin-fortified biscuits were predicted to have the greatest impact in Yaoundé/Douala, with reductions in inadequate intake of 10.3 percentage points (pp) for VA, 12.3 pp for folate, and 3.7 pp for vitamin B12, in the absence of other fortification programs. When existing programs for VA-fortified oil (12 mg VA/kg) and folic acid-fortified wheat flour (5.0 ppm) were considered in the model, the expected marginal impacts of folic acid and VA-fortified biscuits were reduced substantially for both children and WRA. Iron and zinc fortified biscuits were predicted to have no detectable impact on the prevalence of inadequacy among children and WRA for all fortification doses simulated, either in the presence or in the absence of fortified wheat flour. CONCLUSIONS: Given current patterns of biscuit consumption in Cameroon, biscuit fortification at the modeled levels is unlikely to reduce the population prevalence of inadequate intakes. Fortified biscuits may contribute modestly to dietary adequacy of some nutrients (VA and folate) in the absence of staple food fortification programs, particularly in urban areas. FUNDING SOURCES: Mars Co., Michael and Susan Dell Foundation, Sight and Life, and Bill & Melinda Gates Foundation.